Developing a New Clinical Ethics Framework for Rehab: A Pre-Implementation Evaluation from the Perspective of Future Users - Leblanc, Line; Ménard, Sophie; Maïano, Christophe; Perron, Louis; Baril, Catherine; Ouellette-Hughes, Nicole (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2023)
Clinical ethics is widely recognised as an essential contribution to the quality of health and psychosocial service delivery. However, the lack of a common understanding of ethics within teams and insufficient organisational support often limits its optimal integration into the workplace. To address this problem, the clinical ethics committee of a rehabilitation centre developed a new clinical ethics framework based on a theoretical model and conducted a pre-implementation evaluation by interviewing future users. The study estimated the acceptability and initial adoption of the new clinical ethics framework. The quantitative results of the study indicated a high level of acceptability for the definitions, tools and supporting strategies, with the exception of the definition of the concept of ethical issues. The qualitative results showed that the future users perceived positively the attributes of the new framework, such as its benefits and its compatibility with their professional concerns. In addition, they appreciated the fact that the framework was easy to understand and could potentially be applied in daily practice. The suggestions provided by future users also helped to improve the content of the clinical ethics framework. Finally, all the results will be useful for the planification of its eventual implementation.